Newborn screening for vitamin B12 deficiency in Germany: strategies, results, and public health implications - Gramer, Gwendolyn; Fang-Hoffmann, Junmin; Feyh, Patrik; Klinke, Glynis; Monostori, Péter; Mütze, Ulrike; Posset, Roland; Weiss, Karl Heinz; Hoffmann, Georg F.; Okun, Jürgen G. (The journal of pediatrics, 2020)
Objective - To evaluate a systematic newborn screening (NBS) strategy for vitamin B12 deficiency. - Study design - In a prospective single-center NBS study, a systematic screening strategy for vitamin B12 deficiency was developed and evaluated. Tandem-mass spectrometry screening was complemented by 2 second-tier strategies, measuring methylmalonic/3-OH-propionic/methylcitric acid, and homocysteine from dried blood spots. - Results - In a cohort of 176 702 children screened over 27 months, 33 children were detected by NBS in whom (maternal) vitamin B12 deficiency was confirmed. Homocysteine was the most sensitive marker for vitamin B12 deficiency, but only combination with a second-tier strategy evaluating methylmalonic acid allowed for detection of all 33 children. Mothers were of various ethnic origins, and 89% adhered to a balanced diet. Treatment in children was performed predominantly by oral vitamin B12 supplementation (84%), and all children remained without clinical symptoms at short-term follow-up. - Conclusions - Vitamin B12 deficiency is a treatable condition but can cause severe neurologic sequelae in infants if untreated. The proposed screening strategy is feasible and effective to identify moderate and severe cases of vitamin B12 deficiency. With an incidence of 1:5355 newborns, vitamin B12 deficiency is more frequent than inborn errors of metabolism included in NBS panels. Treatment of vitamin B12 deficiency is easy, and additional benefits can be achieved for previously undiagnosed affected mothers. This supports inclusion of vitamin B12 deficiency into NBS but also stresses the need for increased awareness of vitamin B12 deficiency in caregivers of pregnant women.